"Rim‐Differentiated" Pillar[6]arenes. (3rd May 2022) - Chao, Yang; Thikekar, Tushar Ulhas; Fang, Wangjian; Chang, Rong; Xu, Jiong; Ouyang, Nianfeng; Xu, Jun; Gao, Yan; Guo, Minjie; Zuilhof, Han; Sue, Andrew C.‐H.
Abstract: A "rim‐differentiated" pillar[6]arene (RD‐P[6]) was obtained successfully, with the assistance of a dimeric silver trifluoroacetate template, among eight different constitutional isomers in a direct and regioselective manner. The solid‐state conformation of this macrocycle could switch from the 1, 3, 5‐alternate to a truly rim‐differentiated one upon guest inclusion. This highly symmetric RD‐P[6] not only hosts metal‐containing molecules inside its cavity, but also can form a pillar[6]arene‐C60 adduct through co‐crystallization on account of donor‐acceptor interactions. The development of synthetic strategies to desymmetrize pillararenes offers new opportunities for engineering complex molecular architectures and organic electronic materials. Abstract : The use of a dimeric silver trifluoroacetate template, has facilitated a "rim‐differentiated" pillar[6]arene to be isolated successfully from a mixture containing eight constitutional isomers. This macrocycle exhibits interesting conformational adaptation toward guest molecules in the solid state.